Action of corticosteroids in carcinoma of the breast - O´Hara, Herbert (2015)
An account of the mitigating action of corticosteroids in intractable cases of carcinoma of the breast is done. Emphasize the remarkable action of these drugs to improve the general state is the non-use of opioids for pain relief and in some cases even reduced the size of the tumor and healing of skin ulcers.